Severity of the TGN1412 trial disaster cytokine storm correlated with IL‐2 release. (23rd July 2013) - Eastwood, David; Bird, Chris; Dilger, Paula; Hockley, Jason; Findlay, Lucy; Poole, Stephen; Thorpe, Susan J.; Wadhwa, Meenu; Thorpe, Robin; Stebbings, Richard
Abstract : Aim: To determine if cytokine release with a solid phase assay is predictive of adverse responses for a range of therapeutic mAbs. Methods: Cytokine ELISAs and a multi‐array system were used to compare responses generated by different therapeutic mAbs using a solid phase assay. Flow cytometry was employed to determine the cellular source of those cytokines. Results: Only TGN1412 and muromonab‐CD3 stimulated CD4+ T‐cell mediated cytokine release characterized by significant (all P < 0.0001) IFNγ, TNFα, IL‐2, IL‐4, IL‐5, IL‐10, IL‐12, IL‐13, IL‐17 and IL‐22 release, comparable with T‐cell mitogen. Significantly greater ( P < 0.0001) IL‐2 release with TGN1412 (2894–6051 pg ml −1 ) compared with muromonab‐CD3 (62–262 pg ml −1 ) differentiated otherwise comparable cytokine responses. Likewise, TGN1412 stimulated significantly more ( P = 0.0001) IL‐2 producing CD4+ T‐cells than muromonab‐CD3 and induced Th1, Th2, Th17 and Th22 subsets that co‐release this cytokine. Significant TNFα release was observed with bevacizumab ( P = 0.0001), trastuzumab ( P = 0.0031) and alemtuzumab ( P = 0.0177), but no significant IL‐2 release. TGN1412 and muromonab‐CD3 caused pro‐inflammatory cytokine release despite significantly (both P < 0.0001) increasing numbers of T‐cells with a regulatory phenotype. Conclusions: The severity of the adverse response to TGN1412 compared with muromonab‐CD3 and other therapeutic mAbs correlates with the level of IL‐2 release.